Calcium Supplementation Improves Na+/K+ Ratio, Antioxidant Defense and Glyoxalase Systems in Salt-Stressed Rice Seedlings - Rahman, Anisur; Nahar, Kamrun; Hasanuzzaman, Mirza; Fujita, Masayuki (Frontiers in Plant Science, 2016)
The present study investigates the regulatory role of exogenous calcium (Ca) in developing salt stress tolerance in rice seedlings. Hydroponically grown 13-d-old rice (Oryza sativa L. cv. BRRI dhan47) seedlings were exposed to 200 mM NaCl alone and combined with 2 mM CaCl2 and 2 mM ethylene glycol tetraacetic acid (EGTA, a Ca scavenger) for three days. The salt stress caused growth inhibition, chlorosis and water shortage in the rice seedlings. The salt-induced stress disrupted ion homeostasis through Na+ influx and K+ efflux, and decreased other mineral nutrient uptake. Salt-induced stress caused oxidative stress in rice seedlings through lipid peroxidation, loss of plasma membrane integrity, higher reactive oxygen species (ROS) production and methylglyoxal (MG) formation. The salt-stressed rice seedlings supplemented with exogenous Ca recovered from water loss, chlorosis and growth inhibition. Calcium supplementation in the salt-stressed rice seedlings improved ion homeostasis by inhibition of Na+ influx and K+ leakage. Exogenous Ca also improved ROS and MG detoxification by improving the antioxidant defense and glyoxalase systems, respectively. On the other hand, applying EGTA along with salt and Ca again negatively affected the rice seedlings as EGTA negated Ca activity. It confirms that, the positive responses in salt-stressed rice seedlings to exogenous Ca were for Ca mediated improvement of ion homeostasis, antioxidant defense and glyoxalase system.